Effect of Prepared Bio-compost on Plant Growth Promotion Trait of Sorghum - Bambharolia, R. P.; Vyas, Trupti K.; Damasia, D. M.; Deshmukh, A. J. (International Journal of Economic Plants, 2021)
The present study was aimed to test the effect of prepared bio-compost from sugarcane trash (W1) and banana pseudostem (W2) using Bacillus subtilis and Schizophyllum commune on plant growth promotion (PGP) trait of sorghum. Effect of different prepared compost on root length of sorghum was found non-significant at 30 days after sowing in a pot experiment. Whereas, shoot length was significantly affected by substrates (W) and microorganisms (M) in which W2 gave higher shoot length of 24.69 cm while M1 and M3 among microorganisms, were equally found significant for shoot length (26.63 cm) followed by M2 (22.44 cm). Compost prepared by using different substrates had a significant effect on the green and dry biomass yield of sorghum. W2 yielded relatively higher green (8.84 g) and dry (2.03 g) biomass of sorghum. Various growth parameters like shoot length, green and dry biomass were found to increase with the application of compost prepared from banana pseudostem (W2), cellulolytic+lignolytic microorganism (M3) and in unsterilized condition (S0).